2006
DOI: 10.1002/pds.1344
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropics use in the Spanish elderly: predictors and evolution between years 1993 and 2003

Abstract: In Spain, the prevalence of psychoactive drug consumption is higher among elderly women than men, and increases with negative perception of health. The prevalence of consumption was significantly higher in the year 2003.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
2
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 42 publications
(58 reference statements)
6
27
2
18
Order By: Relevance
“…The elderly individuals, in special, are the most frequent users of psychotropic drugs, due to this population's prevalence of psychiatric comorbidities and the use of these drugs in relieving somatic conditions 4,5 . Among elderly Europeans, psychotropic drug use ranged between 20.5 and 29.8% [6][7][8] , numbers higher than those observed among elderly North Americans (14.9 and 19.0%) 3,9 . In the elderly population, the female sex, a negative self-assessment of one's health and the presence of depressive symptom are the characteristics most frequently associated with the use of psychotropic drugs.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The elderly individuals, in special, are the most frequent users of psychotropic drugs, due to this population's prevalence of psychiatric comorbidities and the use of these drugs in relieving somatic conditions 4,5 . Among elderly Europeans, psychotropic drug use ranged between 20.5 and 29.8% [6][7][8] , numbers higher than those observed among elderly North Americans (14.9 and 19.0%) 3,9 . In the elderly population, the female sex, a negative self-assessment of one's health and the presence of depressive symptom are the characteristics most frequently associated with the use of psychotropic drugs.…”
Section: Introductionmentioning
confidence: 83%
“…In the elderly population, the female sex, a negative self-assessment of one's health and the presence of depressive symptom are the characteristics most frequently associated with the use of psychotropic drugs. 6,9,10 Brazilian population-based studies on the use of psychotropic drugs in general (antipsychotics, antidepressants, anxiolytics, and sedatives/hypnotics) are infrequent, and almost all of included a general population sample [11][12][13][14][15] . In Brazil, psychotropic usage ranged between 5.2 and 10.2% among the general population, being greater among older people.…”
Section: Introductionmentioning
confidence: 99%
“…It is more likely that these medications are being used for other therapeutic purposes, such as pain relief, prevention of migraine, management of bipolar disorder, or neurological treatment of patients with a history of stroke 21,30 . In addition, studies in high-income countries 19,20 have shown an increase in the use of psychoactive drugs, both psychoanaleptics and psycholeptics 33 . The current study showed an increase in the use of the former, but not the latter.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, changes in the pattern of use of some drug classes have been observed in some populations, especially in the pattern of consumption of drugs for hypertension 17,18 , as well as an increase in the use of lipid modifying 5,17 , psychoactive 19,20 , and antiepileptic drugs 21 .…”
mentioning
confidence: 99%
“…Já no Canadá e na Espanha, estes são utilizados por mais de 20% dos idosos e, na Austrália, prevalece o seu uso em cerca de 15% (CARRASCO-GARRIDO et al, 2007;HOGAN et al, 2003;WINDLE et al, 2007) Atualmente, apesar desta prática de utilização apresentar-se menos acentuada nos EUA e no Reino Unido, verifica-se uma escala ainda elevada em idosos (GALLACHER et al, 2012). Fator este em modificação, principalmente nos países da Europa, em virtude de programas governamentais de conscientização aos profissionais envolvidos no atendimento ao paciente para promoção de descontinuação acompanhada desta classe farmacológica, visando minimizar os efeitos de abstinência até a sua total extinção (GOULD et al, 2014;HARTHOLT et al, 2011;LADER et al, 2009;SALONOJA et al, 2012;VELERT VILA et al, 2012).…”
Section: Em 2005 Foi Desenvolvido O "Ii Levantamento Domiciliar Sobrunclassified